2003
DOI: 10.1016/j.nuclphysb.2003.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The scalar sector of the Randall–Sundrum model

Abstract: We consider the scalar sector of the Randall-Sundrum model. We derive the effective potential for the Standard Model Higgs-boson sector interacting with Kaluza-Klein excitations of the graviton (h ν n µ ) and the radion (φ) and show that only the Standard Model vacuum solution of ∂V (h)/∂h = 0 (h is the Higgs field) is allowed. We then turn to our main focus: the consequences of the curvaturescalar mixing ξ R H † H (where H is a Higgs doublet field on the visible brane), which causes the physical mass eigensta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
174
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(176 citation statements)
references
References 21 publications
2
174
0
Order By: Relevance
“…We show how in this way one can arrive at an effective Lagrangian that describes the different mixing possibilities encountered in these kinds of models. We also show that moving the Higgs from the brane into the bulk of the extra dimension can already have important consequences on how the radion couples to SM particles, leading to a different radion phenomenology compared to the brane Higgs case [9][10][11][12][13]16]. In particular we show that due to the geometry/conformal symmetry of the radion in the bulk, its couplings to 4D scalar kinetic terms vanish, and therefore the radion coupling to massive gauge bosons is suppressed.…”
Section: Jhep02(2014)032mentioning
confidence: 85%
See 1 more Smart Citation
“…We show how in this way one can arrive at an effective Lagrangian that describes the different mixing possibilities encountered in these kinds of models. We also show that moving the Higgs from the brane into the bulk of the extra dimension can already have important consequences on how the radion couples to SM particles, leading to a different radion phenomenology compared to the brane Higgs case [9][10][11][12][13]16]. In particular we show that due to the geometry/conformal symmetry of the radion in the bulk, its couplings to 4D scalar kinetic terms vanish, and therefore the radion coupling to massive gauge bosons is suppressed.…”
Section: Jhep02(2014)032mentioning
confidence: 85%
“…3 Radion-Higgs mixing Light radion/dilaton phenomenology and mixing with an IR-brane localized Higgs has been studied extensively in the literature [10][11][12][13][14][15]. It has been found that current LHC measurements, in particular of the Higgs mass and signal strengths, already put significant constraints on the parameter space of these models [18][19][20].…”
Section: Jhep02(2014)032mentioning
confidence: 99%
“…Various studies on radion phenomenology have been performed in the past [35,36,101,37,38,102,103,104,105], including recent works where radion dynamics was considered within realistic models of electroweak breaking with bulk SM fields [105,106,107]. For example in the case of radion mass lighter than 2M W , r → γγ is a promising channel [106], which can be also dramatically enhanced in the presence of Higgs-radion mixing [107].…”
Section: Radion Collider Phenomenologymentioning
confidence: 99%
“…Similar analyses were done in ref. [5,28,29,30,31,32,33,34]. We refine the calculations appropriate to the LHC experiments at 7 TeV (LHC7), and consider the possibility of finding φ in the ongoing LHC Higgs searches.…”
Section: Introductionmentioning
confidence: 99%